Supporting students to become autonomous learners: the role of web-based learning. Issue 4 (1st August 2016) - Petra, Siti Fatimah; Jaidin, Jainatul Halida; Perera, JSH Quintus; Linn, Marcia
Abstract : Purpose: We explore how web-based science curriculum materials designed to develop autonomous learners can succeed in Brunei. In this instruction, designed to prepare students to independently explore new topics, students and teachers take new roles. Students collaborate with a peer to engage in inquiry and teachers monitor progress and guide students rather than leading the class. Design/methodology/approach: We studied two Web-based Inquiry Science Environment (WISE) units (photosynthesis and cellular respiration) developed using the knowledge integration framework. The framework promotes autonomous learning by building on the diverse ideas that students bring to science lessons and encouraging them to distinguish among their own ideas and those they encounter when using scientific visualizations (Bransford, Brown & Cocking, 1999). Two intact classes of students from two secondary schools in Brunei each studied one of the WISE units. Observations revealed that students could work in pairs to jointly engage in inquiry with encouragement from teachers. Embedded assessments and interviews were analyzed to show how students linked observable events and scientific ideas when explaining the conversion of solar energy to chemical energy in photosynthesis. Findings: Significant gains in knowledge integration show that Brunei students who collaboratively study WISE inquiry units can autonomously succeed. Specifically, students using WISE were able to construct complex ideas about photosynthesis and cellular respiration by linking observable events and scientific ideas while working autonomously with infrequent teacher monitoring. Originality/value: The paper provides invaluable insights into ways in which web-based learning supports students to become autonomous learners.